An immunomagnetic separation based fluorescence immunoassay for rapid myoglobin quantification in human blood. Issue 40 (30th September 2016) - Wang, Yi; Sun, Hongmei; Li, Rui; Ke, Peng; Zhu, Hongda; Guo, Huiling; Liu, Mingxing; Sun, Honghao
Abstract : Sensitive detection of myoglobin (Myo) in human blood using Myo antibodies 7C3 and 4E2 conjugated to magnetic nanoparticle and fluorescent silica nanoparticle bound Rhodamine Red-X was developed. Abstract : Magnetic nanoparticle (NPs) and fluorescent NP pairs were designed for myoglobin (Myo) detection in human blood. Magnetic NPs MNP@SiO2 @BSA@Au with about 200 nm diameter (by TEM) were prepared through a layer by layer technique following by adsorption of anti-Myo antibody 4E2 on a Au surface. The MNPs were well dispersed in an aqueous solution. Fluorescent NPs were prepared by conjugating fluorescent Rhodamine Red-X (RhX) and another Myo antibody 7C3 on silica NPs with a final diameter of 80 nm. In the presence of Myo, magnetic NPs bearing 4E2 and fluorescent NPs bearing 7C3 form a sandwich structure, which can be separated from blood under a magnetic field. The concentration of Myo is quantified by the fluorescence intensity of SNP@RhX NPs in the sandwich structure. The calibration curve of the Myo showed a linear range between 0 and 250 ng mL −1 ( R 2 = 0.993). The minimum detectable concentration was 0.28 ng mL −1 . The immunomagnetic separation based fluorescence immunoassay offered a simple and accurate way to determine Myo in human blood in 30 min.